The efficiency of higher education institutions in England revisited: comparing alternative measures. Issue 3 (3rd July 2017) - Johnes, Geraint; Tone, Kaoru
Abstract : Data envelopment analysis (DEA) has often been used to evaluate efficiency in the context of higher education institutions. Yet there are numerous alternative non-parametric measures of efficiency available. This paper compares efficiency scores obtained for institutions of higher education in England, 2013–2014, using three different methods: the original Charnes et al. method and two slacks-based methods (SBM-Min and SBM-Max) developed by Tone. The findings suggest that results are highly sensitive to methodology chosen. Hence caution is required in applying the results in any policy context.